The Alkaline Lamprophyres of the Dolomitic Area (Southern Alps, Italy): Markers of the Late Triassic Change from Orogenic-like to Anorogenic Magmatism. (6th June 2019) - Casetta, Federico; Ickert, Ryan B; Mark, Darren F; Bonadiman, Costanza; Giacomoni, Pier Paolo; Ntaflos, Theodoros; Coltorti, Massimo
Abstract: We present the first complete petrological, geochemical and geochronological characterization of the oldest lamprophyric rocks in Italy, which crop out around Predazzo (Dolomitic Area), with the aim of deciphering their relationship with Triassic magmatic events across the whole of the Southern Alps. Their Mg# of between 37 and 70, together with their trace element contents, suggests that fractional crystallization was the main process responsible for their differentiation, together with small-scale mixing, as evidenced by some complex amphibole textures. Moreover, the occurrence of primary carbonate ocelli suggests an intimate association between the alkaline lamprophyric magmas and a carbonatitic melt. 40 Ar/ 39 Ar data show that the lamprophyres were emplaced at 219·22 ± 0·73 Ma (2σ; full systematic uncertainties), around 20 Myr after the high-K calc-alkaline to shoshonitic, short-lived, Ladinian (237–238 Ma) magmatic event of the Dolomitic Area. Their trace element and Sr–Nd isotopic signatures ( 87 Sr/ 86 Sri = 0·7033–0·7040; 143 Nd/ 144 Ndi = 0·51260–0·51265) are probably related to a garnet–amphibole-bearing lithosphere interacting with an asthenospheric component, significantly more depleted than the mantle source of the high-K calc-alkaline to shoshonitic magmas. These features suggest that the Predazzo lamprophyres belong to the same alkaline–carbonatitic magmatic event that intruded the mantle beneath the Southern Alps (e.g. Finero peridotite) between 190 and 225 Ma. In this scenario, the Predazzo lamprophyres cannot be considered as a late-stage pulse of the orogenic-like Ladinian magmatism of the Dolomitic Area, but most probably represent a petrological bridge to the opening of the Alpine Tethys.